Arctic Ocean, expedition crew members shoveling snow - Ellsworth, Lincoln, 1880-1951 (1925)
"No. 20 Amundsen-Ellsworth 1925 Exped. "Where faith abides, through hope be put to flight."" Caption taken from Ellsworth, L., & National Americana Society. (1929). Air Pioneering in the Arctic: the Two Polar Flights of Roald Amundsen and Lincoln Ellsworth (pp. 57, No.20). New York: National Americana Society. Amundsen-Ellsworth 1925 Expedition, "Our only implements, 3 wooden Shovels, a 2-lb. pocket safety-ax and an ice anchor."